Three-Weekly Doses of Azithromycin for Indigenous Infants Hospitalized with Bronchiolitis: A Multicentre, Randomized, Placebo-Controlled Trial - McCallum, Gabrielle B.; Morris, Peter S.; Grimwood, Keith; Maclennan, Carolyn; White, Andrew V.; Chatfield, Mark D.; Sloots, Theo P.; Mackay, Ian M.; Smith-Vaughan, Heidi; McKay, Clare C.; Versteegh, Lesley A.; Jacobsen, Nerida; et al. (Frontiers in Pediatrics, 2015)
Background Bronchiolitis is a major health burden in infants globally, particularly among Indigenous populations. It is unknown if 3-weeks of azithromycin improve clinical outcomes beyond the hospitalisation period. In an international, double-blind randomised controlled trial, we determined if 3-weeks of azithromycin, improved clinical outcomes in Indigenous infants hospitalised with bronchiolitis. Methods Infants aged ≤24-months were enrolled from three centres and randomised to receive three once-weekly doses of either azithromycin (30mg/kg) or placebo. Nasopharyngeal swabs were collected at baseline and 48-hours later. Primary endpoints were hospital length of stay (LOS) and duration of oxygen supplementation monitored every 12-hours until judged ready for discharge. Secondary outcomes were: day-21 symptom/signs, respiratory rehospitalisations within 6-months post-discharge and impact upon nasopharyngeal bacteria and virus shedding at 48-hours. Results Two-hundred-and-nineteen infants were randomised (n=106 azithromycin, n=113 placebo). No significant between-group differences were found for LOS (median 54-hours for each group, difference=0-hours, 95%CI: -6, 8; p=0.8), time receiving oxygen (azithromycin=40-hours, placebo=35-hours, group difference=5-hours, 95%CI: -8, 11; p=0.7), day-21 symptom/signs or rehospitalisation within 6-months (azithromycin n=31, placebo=25 infants, p=0.2). Azithromycin reduced nasopharyngeal bacterial carriage (between-group difference 0.4 bacteria/child, 95%CI: 0.2, 0.6; p<0.001), but had no significant effect upon virus detection rates. Conclusion Despite reducing nasopharyngeal bacterial carriage, three large once-weekly doses of azithromycin did not confer any benefit over placebo during the bronchiolitis illness or 6-months post-hospitalisation. Azithromycin should not be used routinely to treat infants hospitalised with bronchiolitis. Clinical trial registration The trial was registered with the Australian and New Z